Improved phase separation in polymer solar cells by solvent blending. Issue 11 (2nd April 2013) - Kästner, Christian; Muhsin, Burhan; Wild, Andreas; Egbe, Daniel A. M.; Rathgeber, Silke; Hoppe, Harald
ABSTRACT The effect of solvent blending on the performance of an anthracene‐containing poly(p‐phenylene‐ethynylene)‐alt‐poly(p‐phenylene‐vinylene) backbone‐based donor polymer with asymmetrically substituted branched 2‐ethylhexyloxy and methyloxy side‐chains in bulk heterojunction solar cells is reported. This copolymer yields relatively high open‐circuit voltages with fullerene‐based electron acceptors. We systematically studied the thin‐film blend morphology and solar cell performance as a function of solvent composition (chlorobenzene to chloroform ratio) and polymer to [6, 6]‐phenyl C61‐butyric acid methylester (PCBM) ratio. We combined photophysical investigations with atomic force microscopy and grazing incidence wide‐angle X‐ray scattering to elucidate the solid‐state morphology in thin films. In the investigated polymer system, the blend morphology becomes independent of the supporting solvent for high PCBM concentrations. Deposition from solvent blends rather than from pure chlorobenzene facilitates the beneficial phase separation between polymer and PCBM, leading to improved charge transport properties (short‐circuit currents) at lower PCBM concentrations. © 2013 Wiley Periodicals, Inc. J Polym Sci Part B: Polym Phys, 2013, 51, 868–874